Association of sleep duration and incidence of diabetes modified by tea consumption: a report from the Shanghai Men’s Health Study - Dai, Fei (Sleep Med, 2017)
OBJECTIVES: To evaluate the association between sleep duration and the incidence of diabetes stratified by sleep-related factors among Chinese men. METHODS: This study included 34,825 men who provided information on sleep-related questions in the Shanghai Men’s Health Study, a population-based cohort study conducted in Shanghai, China from 2002 to 2011. Participants were excluded who had a history of diabetes or who were diagnosed with diabetes within 2 years of recruitment. Cox regression was employed to evaluate the influence of sleep duration and its interaction with sleep-related factors on diabetes risk. RESULTS: A total of 1521 incident cases were documented during a median of 5.6 follow-up years. Adjusted hazard ratios and 95% confidence intervals were 1.0 (0.9–1.1) and 1.2 (1.0–1.3) for men who slept <7 and ≥8 hours per day, respectively, compared with those who slept 7 hours per day (p(trend)=0.01). Stratified analyses revealed that the association between sleep duration and risk of diabetes was only statistically significant among current smokers and regular drinkers, never tea drinkers, men with a high body mass index, hypertension or comorbidity, and men who did not work nightshift or who snored. A statistically significant interaction between tea drinking and sleep duration was observed (p(interaction)=0.01). The above association patterns remained when daytime nappers were excluded from the analyses. CONCLUSIONS: The data suggested that longer sleep duration, particularly among individuals already exhibiting factors linked to poor quality of sleep, was associated with diabetes. The association between sleep duration and diabetes may be modified by tea drinking, especially in older men or men with more sleep-related factors.